Inactivation of an integrated antibiotic resistance gene in mammalian cells to re-enable antibiotic selection. (April 2014) - Ni, Peiling; Zhang, Qian; Chen, Haixia; Chen, Lingyi
Removing an antibiotic resistance gene allows the same antibiotic to be re-used in the next round of genetic manipulation. Here we applied the CRISPR/Cas system to disrupt the puromycin resistance gene in an engineered mouse embryonic stem cell line and then re-used puromycin selection in the resulting cells to establish stable reporter cell lines. With the CRISPR/Cas system, pre-engineered sequences, such as loxP or FRT, are not required. Thus, this technique can be used to disrupt antibiotic resistance genes that cannot be removed by the Cre-loxP and Flp-FRT systems.